Predictive value of low serum interleukin-33 levels in acute ischemic stroke outcomes - Liu, Wei; Luo, Dongliang; Liu, Xingyu; Zhang, Yuqing; Wang, Zhong (Frontiers in Neurology, 2024)
BackgroundHuman interleukin-33 (IL-33), a member of the IL-1 family, has been identified as a therapeutic target due to its role as a proinflammatory mediator in various diseases. This study aims to evaluate the prognostic value of serum IL-33 levels in patients admitted with their first-ever acute ischemic stroke.MethodsThis single-center, prospective, observational study included 216 patients with acute ischemic stroke. Serum IL-33 levels were measured at hospital admission to assess their predictive value for functional outcomes and mortality within 3 months. IL-33 levels were dichotomized at the median into two groups: the reduced group (IL-33 ≤ median) and the normal group (IL-33 > median).ResultsThe median age of the 216 patients was 66 years (interquartile range [IQR], 56–75), with 132 (61.6%) being women. IL-33 serum levels were inversely correlated with stroke severity, as measured by the National Institutes of Health Stroke Scale (NIHSS) score and lesion size. Patients in the reduced IL-33 group had a higher rate of unfavorable outcomes (55.6% vs. 18.5%; absolute difference, 29.2% [95% confidence interval (CI), 24.5% to 34.4%]; odds ratio (OR), 3.19 [95% CI, 1.72 to 5.91]) and mortality (24.1% vs. 3.7%; absolute difference, 15.8% [95% CI, 13.1% to 18.3%]; OR, 4.12 [95% CI, 1.38 to 12.31]) compared to the normal group. Furthermore, IL-33 levels enhanced the prognostic accuracy of the NIHSS for predicting functional outcomes (combined area under the curve [AUC], 0.84; 95% CI, 0.79–0.84; P < 0.001) and mortality (combined AUC, 0.88; 95% CI, 0.83–0.94; P < 0.001).ConclusionThis study demonstrates that lower IL-33 levels are associated with increased stroke severity and poorer prognosis. These findings suggest that IL-33 may serve as a valuable biomarker for predicting poor outcomes following acute ischemic stroke.